Stratification of disease severity in patients with liver fibrosis, cirrhosis and portal hypertension using novel multiparametric magnetic resonance imaging techniques - Jayaswal, ANA (2019)
Chronic liver diseases (CLDs) affect millions worldwide and are a major cause of mortality. Recently, multiparametric magnetic resonance (MR) methods have been proposed as a non-invasive, quantitative biomarker for assessment of CLD. CLD traverses a spectrum of severity, and the aim of this thesis was to apply MR methods across this spectrum for a quantitative assessment of disease severity. The primary variable of interest was the iron and field strength corrected T1 (cT1), generated by LiverMultiScanTM software from T1 and T2* mapping techniques. Liver cT1 was found to predict liver-related clinical outcomes in patients with CLD (p<0.0001), including in patients with compensated disease only. Liver cT1 performed especially well in patients with non-alcoholic fatty liver disease (NAFLD), alcohol-related liver disease (ArLD) and viral hepatitis (VH) with a cut-off of liver cT1>825ms having a negative predictive value (NPV) of 100%. Liver cT1 quantitatively assessed changes in fibroinflammation in 15 patients with chronic hepatitis C virus (HCV) undergoing treatment by direct acting antiviral (DAA) therapy. Liver cT1 showed significant decreases from baseline to 24 weeks after end of treatment (EoT) (876 vs 806 ms, p=0.002), from baseline to 48 weeks EoT (876 vs 788 ms, p=0.0002) and from 24 weeks EoT to 48 weeks EoT (806 vs 788ms, p=0.016). Spleen cT1 had good diagnostic accuracy for presence of portal hypertension in both an adult cohort with CLD and a paediatric cohort with autoimmune liver disease (area under the receiver operating curve (AUC) of 0.85 and 0.81 respectively). In another adult cohort, spleen cT1 was predictive of future episodes of variceal bleeding (AUC: 0.74), especially in those on non-selective beta-blocker treatments (AUC: 0.97). A reference range for spleen T1 and cT1 was established using data from the United Kingdom Biobank population health study and healthy volunteers from our centre. Higher spleen T1 /cT1 was observed in women vs men and in children vs adults. This thesis provided further evidence that multiparametric MR methods combining T1 and T2* relaxometry can be used across the spectrum of CLD for stratification of disease severity.